UPAYA PENINGKATAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MEMERAS AIR DENGAN MEDIA SPONS KELOMPOK BERMAIN PAUD AL FURQOON MASJID RAYA KLATEN - Siti Khoiriyah Rohimah; Ihda A’yunil Khotimah (STPI Bina Insan Mulia Yogyakarta, 2022)
Fine morotic is the ability to move related to smooth muscles. Early childhooddevelopment is the foundation in carrying out developmental tasks in adulthood. Thisstudy aims to determine the process of implementing the activity of squeezing water withsponge media in improving fine motor skills and to find out how much it increases finemotor skills in the PAUD Al Furqoon Playgroup of Masjid Raya Klaten after theimplementation of these activities. This research method is a Classroom ActionResearch (CAR) with two cycles, each cycle consisting of four stages: planning, actionimplementation, observation, and reflection. Data collection techniques with interviews,observation, performance and documentation. The subjects of this study were the children of the PAUD Al Furqoon Playgroup of the Great Mosque of Klaten, totaling 25children. The results of this study indicate an increase in fine motor skills throughsqueezing water with sponge media in children's Play Group PAUD Al Furqoon MasjidRaya Klaten. The increase in children's motor skills through squeezing water withsponge media are: from pre-cycle 20%, then in the first cycle it increases to 54%, untilthe second cycle the increase is 82%. Then there was an increase of 62%. So it wasconcluded that squeezing water with a sponge media can improve fine motor skills inchildren in the Al Furqoon PAUD Play Group Klaten Grand Mosque.